Passport Photos: By Amitava Kumar, Los Angeles: University of California Press, 2000, 308 pp. (American Journal of Islam and Society, 2000)
What does it mean to be a migrant, to be itinerant, to forever engage in a“dialogue of civilization”? How do migrants make sense of their identity in aworld where every aspect of it is constantly under negotiation by border-keepersand original settlers and earlier immigrants? In his bold new book PassportPhotos, Amitava Kumar, a professor of English at the University of Florida,examines some of the problems faced by diasporic communities through thestudy of an important document, the passport. To the immigrant, the passportis an important intersection between “identity” and “document.” This deep,sensitive and, at times, funny reading of the passport makes for a very thoughtprovokingbook, and I unreserved19 recommend it to anyone who is interestedin a sensitive portrayal of the immigrant experience. The book is like immigrantsthemselves. It speaks in multiple languages, and is obsessed with documents.Among its many tongues, it speaks in academic and political cadences,mixes prose and poetry, sprinkles Urdu and Spanish, quotes Namdeo Dhasal,a poet from India and Louis Arrago, the Mexican poet-activist. It layers Urduupon Spanish, words upon pictures, and best of all, garnishes it with Kumar’spoetry, which is quite magical. There are several poems, each of which is worththe price of admission on a stand-alone basis.In the second paragraph of its preface, the author makes his point clear: “thisbook is a forged passport.” There is, of course, a delightful wordplay here. Wecan read the act of forging as illegal duplication, but we can also read it in termsfamiliar to a blacksmith, the book is forging or creating a new way to understandpassports, borders, being an immigrant and being foreign. As someonewho personally knows several “illegal immigrants,” I used their reality as atouchstone to judge the book. If the book speaks to their condition, withoutromanticizing them or being condescending to them, displaying both theirbravery and their baggage, then it is a good book. If the book cannot reachthem, it is little more than words and I will dismiss it as yet another piece ofdesultory identity politicking.The book certainly fulfiils the above criteria, and much more. It representsthe multilayered experience of immigrants without reducing it to wordplay. At ...